1986
DOI: 10.1111/j.1528-1157.1986.tb03574.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Effects of a Calcium Antagonist (Nimodipine) on Cefazolin‐Induced Epileptogenic Foci in Rabbits

Abstract: The epileptogenic properties of cefazolin (CFZ) were utilized to induce an electrophysiological pattern of epilepsy in the rabbit. CFZ, cortically applied in different concentrations (2 or 4%), produced epileptic activity in a degree proportional to the concentration of the substance. In this experimental epilepsy model, we evaluated the effects of increasing doses (0.025, 0.05, and 0.1 mg/kg i.v.) of the calcium antagonist nimodipine (Bay e 9736). In the evaluation of nimodipine effects, the spike-and-wave bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…This may form the basis of seizures induced by Quin. Therefore, Ca2+ channels in cell soma rather than in nerve terminals were responsible for this disorder, because nimodipine can inhibit Quin-induced seizures (Morocutt et al, 1986;Lu et al, 1990). In these studies, no correlations were found between blocking Ca2 + influx and seizures induced by Quin, even with large doses of daurisoline.…”
Section: Discussionmentioning
confidence: 99%
“…This may form the basis of seizures induced by Quin. Therefore, Ca2+ channels in cell soma rather than in nerve terminals were responsible for this disorder, because nimodipine can inhibit Quin-induced seizures (Morocutt et al, 1986;Lu et al, 1990). In these studies, no correlations were found between blocking Ca2 + influx and seizures induced by Quin, even with large doses of daurisoline.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its vascular action, nimodipine is known to be a potent antagonist of transmembrane calcium influx in cerebral neurons. Since disturbances in neuronal calcium conductance have been implicated in the generation and propagation of seizure activity (Schmidt & Ried, 1989), many investigators have assessed the potential anticonvulsant action of nimodipine in animal models, demonstrating that the drug is effective in preventing and/or supressing seizures induced by a wide variety of chemical (Dolin et al, 1986;Meyer et al, 1987;Morocutti et al, 1986;Paczynsky et al, 1990) and physical (De Sarro et al, 1988;Meyer et al, 1990) stimuli. Preliminary clinical observations support the hypothesis that nimodipine may exert valuable therapeutic effects in patients with seizure disorders (Brandt et al, 1988;De Falce et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…On the hand, Morocutti et al 18) reported that the intravenous injection of calcium antagonist, nimodipine, showed the significant inhibition of the cefazolin-induced epileptogenic foci in rabbits. In addition, nimodipine prevented penicillin-induced seizures in rats.…”
Section: Discussionmentioning
confidence: 99%